Pengaruh Pertumbuhan Usaha Mikro Kecil dan Menengah (UMKM) Terhadap Pertumbuhan Ekonomi Provinsi Jambi Tahun 2020-2022 - As’ad Isma; Victor Diwantara; Fauzi Yudiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2023)
So far, the problems often faced by UMKM are funding problems, and most of their needs are obtained through funding. The development of micro, small and medium enterprises must be reviewed and improved so that problems can be monitored and resolved in a timely manner. Micro, small, and medium enterprises have a strategic role in national economic development, in addition to their role in economic growth and employment. UMKM can be a priority or pillar of a populist economic system that reduces poverty and unemployment, besides that UMKM also plays a role in equitable distribution of development results. So far, the problem that UMKM often face is the problem of funding, and most of their needs are obtained through funding. The development of micro, small and medium enterprises must be reviewed and improved so that if problems arise, they can be monitored and resolved in a timely manner. The problem that is often faced is the situation of entrepreneurs who generally lack working capital loans. This research aims to determine and analyze the effect of UMKM growth on economic growth in Jambi province. The research method used is quantitative. The sample used was 33 data. The results showed that the growth of UMKM had a positive and significant effect on economic growth. In testing the classical assumptions of this study, it is normally distributed, not.